Organisational transformation and scientific change the impact of institutional restructuring on universities and intellectual innovation - Whitley, Richard, 1944-; Glöser, Jochen (Research in the sociology of organizations ;, 2014)
The first part of this book deals with the transformation of universities as strategic organisational actors in some cases creating them as such while the second shows how governance and authority shifts are affecting the kinds of research goals being pursued by academics in different public science systems.